Temporal trends and social inequities in adolescent and young adult mental health disorders in Catalonia, Spain: a 2008–2022 primary care cohort study - Ana Lozano-Sánchez; Enric Aragonès; Tomàs López-Jiménez; Matthew Bennett; Stella Evangelidou; Esther Francisco; Myriam García; Estel Malgosa; Núria Codern-Bové; Claudia Guzmán-Molina; Constanza Jacques-Aviñó (Child and Adolescent Psychiatry and Mental Health)
Abstract Background The prevalence of mental health disorders in children, teens, and young adults is rising at an alarming rate. This study aims to explore time trends in the incidence of mental disorders among young people in Catalonia, Spain from 2008 to 2022, focusing on the effects of the COVID-19 pandemic and from the perspective of social inequities. Methods A cohort study using primary care records from the SIDIAP database was conducted. It included 2,088,641 individuals aged 10 to 24 years. We examined the incidence of depressive, anxiety, eating, and attention deficit/hyperactivity disorders, stratified by sex, age, deprivation, and nationality. Results All disorders reflected an increasing trend throughout the study period: depressive disorders (IRR: 2.44, 95% CI: 2.31–2.59), anxiety disorders (IRR: 2.33, 95% CI: 2.27–2.39), ADHD (IRR: 2.33, 95%CI: 2.17–2.50), and eating disorders (IRR: 3.29, 95% CI: 3.01–3.59). A significant increase in incidence was observed after the outbreak of the COVID-19 pandemic. In 2022, anxiety disorders were most frequent, with an incidence rate (IR) of 2,537 per 100,000 persons-year (95% CI: 2,503–2,571). Depressive disorders followed with an IR of 471 (95% CI: 458–486), ADHD with an IR of 306 (95% CI: 295–317) and eating disorders with an IR of 249 (95% CI: 239–259). Significant associations were reported with sex, age, deprivation, and nationality. Conclusion The incidence of all studied disorders has steadily increased, reaching unprecedented levels during the pandemic. Understanding these trends is essential for an appropriate healthcare response, while addressing the non-medical determinants, requires action across all sectors of society.